Global trends in COVID-19 Alzheimer's related research: a bibliometric analysis - Cao, Chenjun; Li, Sixin; Zhou, Gaoya; Xu, Caijuan; Chen, Xi; Qiu, Huiwen; Li, Xinyu; Liu, Ying; Cao, Hui; Bi, Changlong (Frontiers in Neurology, 2023)
Background The COVID-19 pandemic has significantly impacted public health, putting people with Alzheimer's disease at significant risk. This study used bibliometric analysis method to conduct in-depth research on the relationship between COVID-19 and Alzheimer's disease, as well as to predict its development trends. Methods The Web of Science Core Collection was searched for relevant literature on Alzheimer's and Coronavirus-19 during 2019–2023. We used a search query string in our advanced search. Using Microsoft Excel 2021 and VOSviewer software, a statistical analysis of primary high-yield authors, research institutions, countries, and journals was performed. Knowledge networks, collaboration maps, hotspots, and regional trends were analyzed using VOSviewer and CiteSpace. Results During 2020–2023, 866 academic studies were published in international journals. United States, Italy, and the United Kingdom rank top three in the survey; in terms of productivity, the top three schools were Harvard Medical School, the University of Padua, and the University of Oxford; Bonanni, Laura, from Gabriele d'Annunzio University (Italy), Tedeschi, Gioacchino from the University of Campania Luigi Vanvitelli (Italy), Vanacore, Nicola from Natl Ctr Dis Prevent and Health Promot (Italy), Reddy, P. Hemachandra from Texas Tech University (USA), and El Haj, Mohamad from University of Nantes (France) were the authors who published the most articles; The Journal of Alzheimer's Disease is the journals with the most published articles; “COVID-19,” “Alzheimer's disease,” “neurodegenerative diseases,” “cognitive impairment,” “neuroinflammation,” “quality of life,” and “neurological complications” have been the focus of attention in the last 3 years. Conclusion The disease caused by the COVID-19 virus infection related to Alzheimer's disease has attracted significant attention worldwide. The major hot topics in 2020 were: “Alzheimer' disease,” COVID-19,” risk factors,” care,” and “Parkinson's disease.” During the 2 years 2021 and 2022, researchers were also interested in “neurodegenerative diseases,” “cognitive impairment,” and “quality of life,” which require further investigation.